Meningkatkan Kesadaran Kritis Siswa melalui Strategi Membaca Kritis Teks Naratif - Rizqiani, Diyah Ayu; Herlina, Sari; Astuti, Missi Tri; Novitri, Safriani (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (PKM) aimed to enhance the critical awareness of Madrasah Aliyah students through critical reading strategies using narrative texts. The activity was conducted on February 25, 2025, at MA Diniyah Puteri Pekanbaru and involved 25 tenth-grade students. Students were divided into five small groups and analyzed a narrative text titled "Si Kancil yang Selalu Ingat Tuhan" using worksheets prepared by the PKM team. The program was implemented in three stages: preparation, implementation, and evaluation. Questionnaire results indicated that 92% of students felt the activity helped them better understand the text, and 88% stated they became more accustomed to questioning what they read. The activity was considered engaging and encouraged active participation, effectively fostering students' critical thinking skills. This critical reading strategy using narrative texts can serve as an alternative approach to literacy learning in Islamic senior high schools.